The bumpy trajectory of performance-based financing for healthcare in Sierra Leone: agency, structure and frames shaping the policy process - Maria Paola Bertone; Haja Wurie; Mohamed Samai; Sophie Witter (BMC, 2018)
Abstract Background As performance-based financing (PBF) has been increasingly implemented in low-income countries, a growing literature has developed, assessing its effectiveness and, more recently, focussing on the political dynamics of PBF introduction and implementation. This study contributes to the latter body of literature by exploring decision-making processes on PBF in Sierra Leone during the 2010-2017 period. Sierra Leone presents an interesting case because of the 'start-stop-start' trajectory of PBF. Methods The qualitative case study is based on a document review and 25 key informant interviews with national stakeholders and international actors. Documents and interviews were analysed based on a political economy framework focusing on actors and structure, but also making use of concepts drawn from interpretive policy analysis to look at frames. Results Our analysis describes the process of negotiation and re-negotiation of PBF in Sierra Leone, highlighting the role of different players, both internal and external, their ideas, capacity and power relations, and the shifting narratives around PBF. It is shown that external actors driving the debate make use of 'frames', both actual (i.e., defining the timing and pace of the discussions, the funding available, etc.) and metaphorical (i.e., how PBF is interpreted, defined and understood) to fit in and influence the debate. This is facilitated by the lack of capacity and resources in the fragile setting. Other strategies, such as 'venue shopping' are employed, though they may add to fragmentation in the volatile context. Conclusions The retrospective view of the study has an analytical advantage, but findings are also relevant to guide practice. Although power relations and rent-seeking issues are difficult to overcome in resource and capacity-constrained settings, more attention could be paid to other elements. In particular, adopting shared frames to ensure a common and inclusive understanding of technical concepts such as PBF may be useful to ensure the political sustainability of reforms. Also, the 'actual frames' which define negotiation and implementation should remain flexible, allowing for disrupting events (e.g., the Ebola epidemic in Sierra Leone) as well as for time to develop national capacity and ownership in order to ensure longer-term political support and better health system integration.